Harnessing local creativity for technological advancement: Uncovering MSME innovations rooted in Sumbawa cultural wisdom - Diatmika, I Putu Gede; Rahayu, Sri (Edelweiss Applied Science and Technology, 2025)
This study explores how local creativity and cultural wisdom contribute to strengthening the innovation capacity of Micro, Small, and Medium Enterprises (MSMEs) in Sumbawa, Indonesia, and identifies strategic approaches to improve their production and marketing performance in the digital era. A qualitative descriptive method was employed, with data collected through semi-structured interviews and direct field observations involving MSME actors, cultural stakeholders, and local government officials. Thematic analysis was conducted using a reflexive approach, and data triangulation was applied to ensure validity and analytical rigor. The findings reveal that the incorporation of cultural elements—such as traditional weaving, herbal products, and culinary heritage—enables MSMEs to create culturally distinctive and market-relevant innovations. Additionally, the use of digital marketing tools, including social media and e-commerce platforms, has helped expand market access and improve consumer engagement. Nevertheless, challenges remain, particularly in terms of digital skills and limited infrastructure. The study concludes that the alignment of cultural identity with innovation-driven strategies, supported by capacity-building and institutional collaboration, enhances the competitiveness and sustainability of rural-based MSMEs. These results offer valuable insights into how traditional knowledge and local resources can be effectively utilized to drive inclusive, culture-based economic development in a globalized context.